High-strength wear-resistant flame-retardant antistatic conveyor carrier roller and preparation method thereof

By mixing biomass and flame retardant, graphene flame retardant composites are prepared, combined with polyamide and polyolefins, and high-strength wear-resistant processes are prepared through melt shear dispersion, injection molding and hot pressing processes. The flame-retardant and anti-static conveyor rollers solve the problems of flammable, poor wear resistance, poor corrosion resistance and insufficient thermal conductivity in the prior art, and achieves efficient and safe roller performance improvement.

CN119431931APending Publication Date: 2025-02-14SHENHUA SHENDONG COAL GRP +3
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411808562.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-02-14

Smart Images

  • Figure CN119431931A_ABST
    Figure CN119431931A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of polyolefin composite materials, and particularly relates to a high-strength wear-resistant flame-retardant antistatic conveyor carrier roller and a preparation method thereof. Biomass and a flame retardant are mixed and then subjected to instantaneous high-temperature treatment, a graphene flame-retardant complex is prepared, the graphene flame-retardant complex, polyamide, a compatilizer and polyolefin serve as raw materials, the polyolefin is modified through the graphene flame-retardant complex and polyamide, blending of the raw materials is promoted through the compatilizer, and the flame-retardant composite material is obtained. And carrying out melt shearing dispersion, injection molding and hot pressing to obtain the high-strength wear-resistant flame-retardant antistatic conveyor carrier roller. The high-strength wear-resistant flame-retardant antistatic conveyor carrier roller obtained by the method has the characteristics of static resistance, wear resistance, high strength and flame retardance, and overcomes the technical defects of the carrier roller prepared by blending a non-metallic material and a flame retardant in the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyolefin composite materials, and particularly relates to a high-strength, wear-resistant, flame-retardant and antistatic conveyor roller and a preparation method thereof. Background Art

[0002] In modern industrial production, conveyor rollers are an important part of equipment. Their main function is to support and transport various materials during the conveying process. The performance of rollers directly affects the efficiency and reliability of the entire conveying system. With the continuous development of industrial production, the performance requirements for rollers are getting higher and higher, especially for those applications that require high temperature, high pressure, and corrosive environments, such as mining, metallurgy, and chemical industries.

[0003] Traditional conveyor rollers are usually made of metal materials (such as steel rollers) or non-metallic materials (such as ceramic rollers). However, rollers made of metal materials have some limitations, such as heavy weight, easy to rust, and high cost. Therefore, the existing technology mainly studies the use of non-metallic materials to make rollers. However, non-metallic materials are flammable. In order to improve the flame retardant properties of rollers made of non-metallic materials, most of the existing technologies consider mixing flame retardants with non-metallic materials. However, due to the defect that flame retardants are easy to agglomerate, in order to achieve the preparation of products with good flame retardant properties in the existing technology, a common practice is to add flame retardants. However, due to the problem of agglomeration, the flame retardant effect of the flame retardant is reduced. In order to achieve flame retardant properties, the amount of flame retardant added may even reach 50% of the main material, which leads to waste of flame retardant. Summary of the invention

[0004] In view of the deficiencies in the above-mentioned prior art, the present invention provides a high-strength, wear-resistant, flame-retardant and antistatic conveyor roller and a preparation method thereof. The present invention mixes biomass and flame retardant and then performs instant high-temperature treatment to obtain a graphene flame-retardant composite, and then uses the graphene flame-retardant composite, polyamide, compatibilizer and polyolefin as raw materials, modifies polyolefin by the graphene flame-retardant composite and polyamide, and obtains a high-strength, wear-resistant, flame-retardant and antistatic conveyor roller through melt shear dispersion, injection molding and hot pressing. The high-strength, wear-resistant, flame-retardant and antistatic conveyor roller obtained by the method of the present invention has excellent flame retardant properties while adding a small amount of flame retardant, overcoming the technical defects of the prior art of using non-metallic materials to prepare rollers.

[0005] To achieve the above object, the technical solution of the present invention is as follows:

[0006] After the biomass and the flame retardant are mixed, they are subjected to instantaneous high-temperature treatment. While the graphene polymer is prepared by the biomass, the flame retardant is adsorbed on the graphene polymer to obtain a graphene flame-retardant composite.

[0007] The weight percentages of the raw materials are: 5-20% of the flame retardant, 80-95% of the biomass, and the sum of the weight percentages of the two is 100%.

[0008] The graphene flame retardant composite, polyamide, a compatibilizer and polyolefin are mixed to obtain a mixture.

[0009] The weight percentages of the raw materials are: 5-10% of graphene flame retardant composite, 5-10% of polyamide, 2±0.1% of compatibilizer, and the balance is polyolefin. The sum of the weight percentages of the raw materials is 100%.

[0010] The mixed material is melted and sheared and dispersed to obtain a composite material.

[0011] The composite material is sequentially subjected to injection molding and hot pressing to obtain a high-strength, wear-resistant, flame-retardant and antistatic conveyor roller.

[0012] Preferably, the biomass material is selected from one or more of straw, bamboo, and corn cobs.

[0013] Preferably, the conditions for the instantaneous high temperature treatment are: treatment at 2000-3500° C. for 30-50 ms.

[0014] Preferably, the flame retardant is selected from at least one of phosphorus-based flame retardants, metal hydroxides, and ammonia-based flame retardants.

[0015] Preferably, the conditions for melt shear dispersion are: 180-300°C, 1-5MPa.

[0016] Preferably, the polyamide is selected from one or more of nylon 6, nylon 66, nylon 11 and nylon 12.

[0017] Preferably, the compatibilizer is selected from one or more of maleic anhydride, dicumyl peroxide, ethylene-acrylate, and polyolefin elastomer.

[0018] Preferably, the olefin is selected from polyolefins selected from one or more of high-density polyethylene, linear low-density polyethylene, isotactic polypropylene, syndiotactic polypropylene, and atactic polypropylene.

[0019] Preferably, a lubricant is added during the preparation of the mixture to promote compatibility between the raw materials. The lubricant is selected from polyethylene wax oil, paraffin oil, white oil or vinyl bisstearylamide, and the mass percentage of the lubricant in the composite material is 3-5%.

[0020] Preferably, an auxiliary agent is added during the preparation of the mixture, and the auxiliary agent consists of antioxidant 1010 and antioxidant 168. The mass percentage of antioxidant 1010 and antioxidant 168 in the composite material is 1±0.1%. The combined use of antioxidant 1010 and antioxidant 168 can enhance each other's antioxidant effect, thereby improving the antioxidant performance of the entire system.

[0021] Preferably, the injection molding conditions are: 180-220°C, 5-15MPa.

[0022] Preferably, the hot pressing conditions are: 200-250°C, 1-5MPa.

[0023] The present invention also protects the high-strength, wear-resistant, flame-retardant and antistatic conveyor roller prepared by the preparation method.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. The present invention uses biomass and flame retardant as raw materials, mixes the two and then performs instantaneous high-temperature treatment. While using biomass to prepare graphene polymer, the flame retardant is adsorbed on the graphene polymer. Graphene has a large specific surface area, which realizes the dispersion of the flame retardant and inhibits the agglomeration of the flame retardant to obtain a graphene flame retardant composite. Then, the graphene flame retardant composite, polyamide, compatibilizer and polyolefin are used as raw materials, and after melt shear dispersion, injection molding and hot pressing, polyolefin is used as a matrix, and the polyolefin is modified by using the graphene flame retardant composite and polyamide. The compatibilizer is used to promote the blending of the raw materials to obtain a high-strength, wear-resistant, flame-retardant and antistatic conveyor roller. In the high-strength, wear-resistant, flame-retardant and antistatic conveyor roller, since the graphene flame retardant composite is a whole and graphene inhibits the agglomeration of the flame retardant, the flame retardant has excellent flame retardant properties while being added in small amounts, thereby overcoming the problem of flame retardant waste caused by direct blending in the prior art.

[0026] 2. The non-metallic rollers in the prior art have poor wear resistance and corrosion resistance. The burrs caused by wear during use will damage the belt. At the same time, the heavy weight will cause large running resistance and generate noise. The present invention uses polyolefin as the matrix, and uses a graphene flame retardant composite in combination with polyamide to modify the polyolefin. By regulating the temperature and pressure of melt shear dispersion, the in-situ fiberization of polyamide and polyolefin is achieved. Specifically, during the processing, when the polyamide is subjected to shear force in the polyolefin matrix, it will undergo deformation such as stretching and orientation, and its molecular chains will be arranged along the force direction to form a fibrous structure. At the same time, the shear force makes the polyamide phase better dispersed in the polyolefin to prevent it from agglomerating, which is conducive to the formation of fine and uniform fibers, improves the wear resistance, and obtains a high-strength wear-resistant, flame-retardant and anti-static conveyor roller with light weight, low cost, good wear resistance, good corrosion resistance, low running resistance and low noise.

[0027] 3. The non-metallic rollers in the prior art have poor thermal and electrical conductivity and are prone to generate static electricity, which poses certain safety hazards in specific environments. The present invention utilizes the excellent thermal and electrical conductivity of graphene in the graphene flame retardant composite to obtain a roller with good thermal and electrical conductivity, which effectively prevents the generation of static electricity and improves safety of use. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Schematic diagram of in situ fiberization of polyamide and polyolefin.

[0029] Figure 2 This is a flow chart for preparing high-strength, wear-resistant, flame-retardant and antistatic conveyor rollers according to Examples 1-5 of the present invention. DETAILED DESCRIPTION

[0030] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention. The experimental methods described in the embodiments of the present invention are conventional methods unless otherwise specified.

[0031] Taking into account the problem that the prior art directly blends flame retardants with non-metallic materials, resulting in flame retardant agglomeration, which in turn results in flame retardant waste, the present invention uses biomass and flame retardants as raw materials, realizes the transformation of biomass into treasure, and obtains a graphene flame retardant composite through instantaneous high-temperature treatment. The graphene flame retardant composite not only has the excellent properties of graphene, but also inhibits the agglomeration of flame retardants, so that the roller obtained by using the graphene flame retardant composite has the characteristics of high strength, wear resistance, flame retardancy and antistatic.

[0032] The technical solution of the present invention is studied using embodiments and comparative examples below, and the specific research methods and results are as follows:

[0033] Example 1

[0034] A method for preparing a high-strength, wear-resistant, flame-retardant and antistatic conveyor roller comprises the following steps:

[0035] S1. After mixing the straw and the flame retardant, subjecting the mixture to instantaneous high temperature treatment at 3000° C. for 40 ms to obtain a graphene flame retardant composite.

[0036] The mass percentage of the flame retardant is 10%, and the mass percentage of the straw is 90%.

[0037] S2. Weigh the raw materials according to the following weight percentages: 8% graphene flame retardant composite, 67% nylon, 2% maleic anhydride, 10101% antioxidant, 1681% antioxidant, 4% vinyl bisstearyl amide, and the remainder is high-density polyethylene. The sum of the weight percentages of the raw materials is 100%.

[0038] S3, putting the graphene-graphene flame retardant composite, nylon 6, maleic anhydride, antioxidant 1010, antioxidant 168, vinyl bisstearyl amide and high-density polyethylene into a high-speed mixer and mixing at high speed for 3 minutes to obtain a mixture.

[0039] S4. Put the mixed material into a twin-screw extruder, and set different temperatures at equal intervals on the screw of the twin-screw extruder, specifically: 180°C, 200°C, 210°C, 230°C, 260°C, 230°C, 210°C, 200°C, 200°C, 200°C, and carry out melt shear dispersion under the conditions of 2 MPa and a shear rate of 350 rpm to obtain a composite material.

[0040] S5. Put the composite material into an injection molding machine, set different temperatures at equal intervals on the screw, specifically: 180°C, 190°C, 200°C, 210°C, 220°C, after injection molding under a pressure of 50MPa, place it in a hot press, and solidify it at a temperature of 220°C and a pressure of 4MPa to obtain a high-strength, wear-resistant, flame-retardant and antistatic conveyor roller. The dimensions of the high-strength, wear-resistant, flame-retardant and antistatic conveyor roller are: diameter 50mm, length 100mm.

[0041] Example 2

[0042] A method for preparing a high-strength, wear-resistant, flame-retardant and antistatic conveyor roller comprises the following steps:

[0043] S1. After mixing the straw and the flame retardant, subjecting the mixture to instantaneous high temperature treatment at 3000° C. for 40 ms to obtain a graphene flame retardant composite.

[0044] The mass percentage of the flame retardant is 10%, and the mass percentage of the straw is 90%.

[0045] S2. Weigh the raw materials according to the following weight percentages: 8% graphene flame retardant composite, 67% nylon, 2% maleic anhydride, 10101% antioxidant, 1681% antioxidant, 4% vinyl bisstearylamide, and the remainder is low-density linear polyethylene. The sum of the weight percentages of the raw materials is 100%.

[0046] S3. Put the graphene flame retardant composite, nylon 6, maleic anhydride, antioxidant 1010, antioxidant 168, vinyl bisstearyl amide and low-density linear polyethylene into a high-speed mixer and mix at high speed for 3 minutes to obtain a mixture.

[0047] S4. Put the mixed material into a twin-screw extruder, and set different temperatures at equal intervals on the screw of the twin-screw extruder, specifically: 180°C, 200°C, 210°C, 230°C, 260°C, 230°C, 210°C, 200°C, 200°C, 200°C, 2MPa, and carry out melt shear dispersion under the conditions of 2MPa and shear rate of 350rpm to obtain a composite material.

[0048] S5. Put the composite material into an injection molding machine, set different temperatures at equal intervals on the screw, specifically: 180°C, 190°C, 200°C, 210°C, 220°C, after injection molding under a pressure of 50MPa, place it in a hot press, and solidify it at a temperature of 220°C and a pressure of 4MPa to obtain a high-strength, wear-resistant, flame-retardant and antistatic conveyor roller. The dimensions of the high-strength, wear-resistant, flame-retardant and antistatic conveyor roller are: diameter 50mm, length 100mm.

[0049] Example 3

[0050] A method for preparing a high-strength, wear-resistant, flame-retardant and antistatic conveyor roller comprises the following steps:

[0051] S1. After mixing the straw and the flame retardant, subjecting the mixture to instantaneous high temperature treatment at 3000° C. for 40 ms to obtain a graphene flame retardant composite.

[0052] The mass percentage of the flame retardant is 10%, and the mass percentage of the straw is 90%.

[0053] S2. Weigh the raw materials according to the following weight percentages: 8% graphene flame retardant composite, 67% nylon, 2% maleic anhydride, 10101% antioxidant, 1681% antioxidant, 4% vinyl bisstearylamide, and the remainder is isotactic polypropylene. The sum of the weight percentages of the raw materials is 100%.

[0054] S3. Put the graphene flame retardant composite, nylon 6, maleic anhydride, antioxidant 1010, antioxidant 168, vinyl bisstearyl amide and isotactic polypropylene into a high-speed mixer and mix at high speed for 3 minutes to obtain a mixture.

[0055] S4. Put the mixed material into a twin-screw extruder, and set different temperatures at equal intervals on the screw of the twin-screw extruder, specifically: 180°C, 200°C, 210°C, 230°C, 300°C, 260°C, 230°C, 200°C, 200°C, 200°C, and carry out melt shear dispersion under the conditions of 2 MPa and a shear rate of 350 rpm to obtain a composite material.

[0056] S5. Put the composite material into an injection molding machine, set different temperatures at equal intervals on the screw, specifically: 180°C, 190°C, 200°C, 210°C, 220°C, after injection molding under a pressure of 50MPa, place it in a hot press, and solidify it at a temperature of 220°C and a pressure of 4MPa to obtain a high-strength, wear-resistant, flame-retardant and antistatic conveyor roller. The dimensions of the high-strength, wear-resistant, flame-retardant and antistatic conveyor roller are: diameter 50mm, length 100mm.

[0057] Example 4

[0058] A method for preparing a high-strength, wear-resistant, flame-retardant and antistatic conveyor roller comprises the following steps:

[0059] S1. After mixing the straw and the flame retardant, subjecting the mixture to instantaneous high temperature treatment at 2000° C. for 50 ms to obtain a graphene flame retardant composite.

[0060] The mass percentage of the flame retardant is 5%, and the mass percentage of the straw is 95%.

[0061] S2. Weigh the raw materials according to the following weight percentages: 10% graphene flame retardant composite, 65% nylon, 2.1% maleic anhydride, 10101.1% antioxidant, 1680.9% antioxidant, 3% vinyl bisstearylamide, and the remainder is low-density linear polyethylene. The sum of the weight percentages of the raw materials is 100%.

[0062] S3. Put the graphene flame retardant composite, nylon 66, maleic anhydride, antioxidant 1010, antioxidant 168, vinyl bisstearyl amide and low-density linear polyethylene into a high-speed mixer and mix at high speed for 3 minutes to obtain a mixture.

[0063] S4. Put the mixed material into a twin-screw extruder, and set different temperatures at equal intervals on the screw of the twin-screw extruder, specifically: 180°C, 200°C, 210°C, 230°C, 260°C, 230°C, 210°C, 200°C, 200°C, 200°C, 2MPa, and carry out melt shear dispersion under the conditions of 2MPa and shear rate of 350rpm to obtain a composite material.

[0064] S5. Put the composite material into an injection molding machine, set different temperatures at equal intervals on the screw, specifically: 180°C, 190°C, 200°C, 210°C, 220°C, after injection molding under a pressure of 50MPa, place it in a hot press, and solidify it at a temperature of 220°C and a pressure of 4MPa to obtain a high-strength, wear-resistant, flame-retardant and antistatic conveyor roller. The dimensions of the high-strength, wear-resistant, flame-retardant and antistatic conveyor roller are: diameter 50mm, length 100mm.

[0065] Example 5

[0066] A method for preparing a high-strength, wear-resistant, flame-retardant and antistatic conveyor roller comprises the following steps:

[0067] S1. After mixing the straw and the flame retardant, subjecting the mixture to instantaneous high temperature treatment at 3500° C. for 30 ms to obtain a graphene flame retardant composite.

[0068] The mass percentage of the flame retardant is 20%, and the mass percentage of the straw is 80%.

[0069] S2. Weigh the raw materials according to the following weight percentages: 5% graphene flame retardant composite, 10% nylon 6, 1.9% maleic anhydride, 10% antioxidant 0.9%, 16% antioxidant 81.1%, 5% vinyl bisstearylamide, and the remainder is low-density linear polyethylene. The sum of the weight percentages of the raw materials is 100%.

[0070] S3. Put the graphene flame retardant composite, nylon 66, maleic anhydride, antioxidant 1010, antioxidant 168, vinyl bisstearyl amide and low-density linear polyethylene into a high-speed mixer and mix at high speed for 3 minutes to obtain a mixture.

[0071] S4. Put the mixed material into a twin-screw extruder, and set different temperatures at equal intervals on the screw of the twin-screw extruder, specifically: 180°C, 200°C, 210°C, 230°C, 260°C, 230°C, 210°C, 200°C, 200°C, 200°C, 2MPa, and carry out melt shear dispersion under the conditions of 2MPa and shear rate of 350rpm to obtain a composite material.

[0072] S5. Put the composite material into an injection molding machine, set different temperatures at equal intervals on the screw, specifically: 180°C, 190°C, 200°C, 210°C, 220°C, after injection molding under a pressure of 50MPa, place it in a hot press, and solidify it at a temperature of 220°C and a pressure of 4MPa to obtain a high-strength, wear-resistant, flame-retardant and antistatic conveyor roller. The dimensions of the high-strength, wear-resistant, flame-retardant and antistatic conveyor roller are: diameter 50mm, length 100mm.

[0073] Example 6

[0074] A method for preparing a high-strength, wear-resistant, flame-retardant and antistatic conveyor roller, which has the same preparation steps as those in Example 1, except that the method does not contain antioxidant 1010, antioxidant 168 and vinyl bisstearylamide, and comprises the following steps:

[0075] S1. After mixing the straw and the flame retardant, subjecting the mixture to instantaneous high temperature treatment at 3000° C. for 40 ms to obtain a graphene flame retardant composite.

[0076] The mass percentage of the flame retardant is 10%, and the mass percentage of the straw is 90%.

[0077] S2. Weigh the raw materials according to the following weight percentages: 8% of graphene flame retardant composite, 67% of nylon, 2% of maleic anhydride, and the balance is high-density polyethylene. The sum of the weight percentages of the raw materials is 100%.

[0078] S3, putting the graphene-graphene flame retardant composite, nylon 6, maleic anhydride and high-density polyethylene into a high-speed mixer and mixing at high speed for 3 minutes to obtain a mixture.

[0079] S4. Put the mixed material into a twin-screw extruder, and set different temperatures at equal intervals on the screw of the twin-screw extruder, specifically: 180°C, 200°C, 210°C, 230°C, 260°C, 230°C, 210°C, 200°C, 200°C, 200°C, and carry out melt shear dispersion under the conditions of 2 MPa and a shear rate of 350 rpm to obtain a composite material.

[0080] S5. Put the composite material into an injection molding machine, set different temperatures at equal intervals on the screw, specifically: 180°C, 190°C, 200°C, 210°C, 220°C, after injection molding under a pressure of 50MPa, place it in a hot press, and solidify it at a temperature of 220°C and a pressure of 4MPa to obtain a high-strength, wear-resistant, flame-retardant and antistatic conveyor roller. The dimensions of the high-strength, wear-resistant, flame-retardant and antistatic conveyor roller are: diameter 50mm, length 100mm.

[0081] Example 7

[0082] A method for preparing a high-strength, wear-resistant, flame-retardant and antistatic conveyor roller, which has the same preparation steps as those of Example 2, except that the method does not contain antioxidant 1010, antioxidant 168 and vinyl bisstearylamide, and comprises the following steps:

[0083] S1. After mixing the straw and the flame retardant, subjecting the mixture to instantaneous high temperature treatment at 3000° C. for 40 ms to obtain a graphene flame retardant composite.

[0084] The mass percentage of the flame retardant is 10%, and the mass percentage of the straw is 90%.

[0085] S2. Weigh the raw materials according to the following weight percentages: 8% of graphene flame retardant composite, 67% of nylon, 2% of maleic anhydride, and the balance is low-density linear polyethylene. The sum of the weight percentages of the raw materials is 100%.

[0086] S3. Put the graphene flame retardant composite, nylon 6, maleic anhydride and low-density linear polyethylene into a high-speed mixer and mix them at high speed for 3 minutes to obtain a mixture.

[0087] S4. Put the mixed material into a twin-screw extruder, and set different temperatures at equal intervals on the screw of the twin-screw extruder, specifically: 180°C, 200°C, 210°C, 230°C, 260°C, 230°C, 210°C, 200°C, 200°C, 200°C, 2MPa, and carry out melt shear dispersion under the conditions of 2MPa and shear rate of 350rpm to obtain a composite material.

[0088] S5. Put the composite material into an injection molding machine, set different temperatures at equal intervals on the screw, specifically: 180°C, 190°C, 200°C, 210°C, 220°C, after injection molding under a pressure of 50MPa, place it in a hot press, and solidify it at a temperature of 220°C and a pressure of 4MPa to obtain a high-strength, wear-resistant, flame-retardant and antistatic conveyor roller. The dimensions of the high-strength, wear-resistant, flame-retardant and antistatic conveyor roller are: diameter 50mm, length 100mm.

[0089] Example 8

[0090] A method for preparing a high-strength, wear-resistant, flame-retardant and antistatic conveyor roller, which has the same preparation steps as those in Example 3, except that the method does not contain antioxidant 1010, antioxidant 168 and vinyl bisstearylamide, and comprises the following steps:

[0091] S1. After mixing the straw and the flame retardant, subjecting the mixture to instantaneous high temperature treatment at 3000° C. for 40 ms to obtain a graphene flame retardant composite.

[0092] The mass percentage of the flame retardant is 10%, and the mass percentage of the straw is 90%.

[0093] S2. Weigh the raw materials according to the following weight percentages: 8% of graphene flame retardant composite, 67% of nylon, 2% of maleic anhydride, and the remainder is isotactic polypropylene. The sum of the weight percentages of the raw materials is 100%.

[0094] S3. Put the graphene flame retardant composite, nylon 6, maleic anhydride and isotactic polypropylene into a high-speed mixer and mix them at high speed for 3 minutes to obtain a mixture.

[0095] S4. Put the mixed material into a twin-screw extruder, and set different temperatures at equal intervals on the screw of the twin-screw extruder, specifically: 180°C, 200°C, 210°C, 230°C, 300°C, 260°C, 230°C, 200°C, 200°C, 200°C, and carry out melt shear dispersion under the conditions of 2 MPa and a shear rate of 350 rpm to obtain a composite material.

[0096] S5. Put the composite material into an injection molding machine, set different temperatures at equal intervals on the screw, specifically: 180°C, 190°C, 200°C, 210°C, 220°C, after injection molding under a pressure of 50MPa, place it in a hot press, and solidify it at a temperature of 220°C and a pressure of 4MPa to obtain a high-strength, wear-resistant, flame-retardant and antistatic conveyor roller. The dimensions of the high-strength, wear-resistant, flame-retardant and antistatic conveyor roller are: diameter 50mm, length 100mm.

[0097] Comparative Example 1

[0098] A method for preparing a high-strength, wear-resistant, flame-retardant and antistatic conveyor roller, which has the same preparation steps as those in Example 1, except that no graphene flame-retardant composite is used in the raw material, comprises the following steps:

[0099] S1. Weigh the raw materials according to the following weight percentages: 67% nylon, 2% maleic anhydride, 10101% antioxidant, 1681% antioxidant, 4% vinyl bisstearylamide, and the remainder is high-density polyethylene. The sum of the weight percentages of the raw materials is 100%.

[0100] S2. Put nylon 6, maleic anhydride, antioxidant 1010, antioxidant 168, vinyl bisstearyl amide and high-density polyethylene into a high-speed mixer and mix at high speed for 3 minutes to obtain a mixture.

[0101] S3. Put the mixed material into a twin-screw extruder, and set different temperatures at equal intervals on the screw of the twin-screw extruder, specifically: 180°C, 200°C, 210°C, 230°C, 260°C, 230°C, 210°C, 200°C, 200°C, 200°C, and carry out melt shear dispersion under the conditions of 2 MPa and a shear rate of 350 rpm to obtain a composite material.

[0102] S4. Put the composite material into an injection molding machine, set different temperatures at equal intervals on the screw, specifically: 180°C, 190°C, 200°C, 210°C, 220°C, after injection molding under a pressure of 50MPa, place it in a hot press, and solidify it at a temperature of 220°C and a pressure of 4MPa to obtain a high-strength, wear-resistant, flame-retardant and antistatic conveyor roller. The dimensions of the high-strength, wear-resistant, flame-retardant and antistatic conveyor roller are: diameter 50mm, length 100mm.

[0103] Comparative Example 2

[0104] A method for preparing a high-strength, wear-resistant, flame-retardant and antistatic conveyor roller, which has the same preparation steps as those in Example 2, except that no graphene flame-retardant composite is used in the raw material, comprises the following steps:

[0105] S1. Weigh the raw materials according to the following weight percentages: 67% nylon, 2% maleic anhydride, 10101% antioxidant, 1681% antioxidant, 4% vinyl bisstearylamide, and the remainder is low-density linear polyethylene. The sum of the weight percentages of the raw materials is 100%.

[0106] S2. Put nylon 6, maleic anhydride, antioxidant 1010, antioxidant 168, vinyl bisstearyl amide and low-density linear polyethylene into a high-speed mixer and mix at high speed for 3 minutes to obtain a mixture.

[0107] S3. Put the mixed material into a twin-screw extruder, and set different temperatures at equal intervals on the screw of the twin-screw extruder, specifically: 180°C, 200°C, 210°C, 230°C, 260°C, 230°C, 210°C, 200°C, 200°C, 200°C, 2MPa, and carry out melt shear dispersion under the conditions of 2MPa and shear rate of 350rpm to obtain a composite material.

[0108] S4. Put the composite material into an injection molding machine, set different temperatures at equal intervals on the screw, specifically: 180°C, 190°C, 200°C, 210°C, 220°C, after injection molding under a pressure of 50MPa, place it in a hot press, and solidify it at a temperature of 220°C and a pressure of 4MPa to obtain a high-strength, wear-resistant, flame-retardant and antistatic conveyor roller. The dimensions of the high-strength, wear-resistant, flame-retardant and antistatic conveyor roller are: diameter 50mm, length 100mm.

[0109] Comparative Example 3

[0110] A method for preparing a high-strength, wear-resistant, flame-retardant and antistatic conveyor roller, which has the same preparation steps as those in Example 3, except that no graphene flame-retardant composite is used in the raw material, comprises the following steps:

[0111] S1. Weigh the raw materials according to the following weight percentages: 67% nylon, 2% maleic anhydride, 10101% antioxidant, 1681% antioxidant, 4% vinyl bisstearylamide, and the remainder is isotactic polypropylene. The sum of the weight percentages of the raw materials is 100%.

[0112] S2. Put nylon 6, maleic anhydride, antioxidant 1010, antioxidant 168, vinyl bisstearyl amide and isotactic polypropylene into a high-speed mixer and mix at high speed for 3 minutes to obtain a mixture.

[0113] S3. Put the mixed material into a twin-screw extruder, and set different temperatures at equal intervals on the screw of the twin-screw extruder, specifically: 180°C, 200°C, 210°C, 230°C, 300°C, 260°C, 230°C, 200°C, 200°C, 200°C, and carry out melt shear dispersion under the conditions of 2 MPa and a shear rate of 350 rpm to obtain a composite material.

[0114] S4. Put the composite material into an injection molding machine, set different temperatures at equal intervals on the screw, specifically: 180°C, 190°C, 200°C, 210°C, 220°C, after injection molding under a pressure of 50MPa, place it in a hot press, and solidify it at a temperature of 220°C and a pressure of 4MPa to obtain a high-strength, wear-resistant, flame-retardant and antistatic conveyor roller. The dimensions of the high-strength, wear-resistant, flame-retardant and antistatic conveyor roller are: diameter 50mm, length 100mm.

[0115] According to needs, the present invention can also perform surface treatment on the obtained high-strength wear-resistant, flame-retardant and anti-static conveyor roller, such as coating an antioxidant or an anti-ultraviolet agent, to further improve its weather resistance and service life.

[0116] The high-strength, wear-resistant, flame-retardant and antistatic conveyor rollers obtained in Examples 1-3 and Comparative Examples 1-3 of the present invention are tested as follows:

[0117] The composite material was dried at 100°C for 1-2h, and then the composite material was molded using an injection molding machine equipped with a standard test specimen mold. Each group of composite materials contained 5 tensile test specimens and 3 flame retardant test specimens.

[0118] Mechanical properties test: According to the plastic tensile properties test standard ASTM D638-2003 of the American Society for Testing and Materials, the tensile properties of the composite materials were tested using a universal tensile machine (model 5900) from Instron, USA. At least three parallel samples were tested in each group, and the average value of the results was taken.

[0119] Flame retardant performance test: Tested according to UL94 flame retardant standard and test method, at least 3 parallel samples are tested in each group.

[0120] The test results are shown in Table 1:

[0121] Table 1 Performance test results

[0122]

[0123] According to the test results of mechanical properties, after polyolefin is modified by adding graphene flame retardant composite and polyamide, the hardness of the material is improved by no less than 15% compared with the composite material of polyolefin and polyamide without adding graphene flame retardant composite, which reflects that the wear resistance of the modified composite material is significantly improved; at the same time, according to the test of surface resistance and flame retardant grade, the composite materials of polyolefin and polyamide without adding graphene flame retardant composite are significantly improved.

[0124] Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing a high-strength, wear-resistant, flame-retardant and antistatic conveyor roller, characterized in that: The steps include: After the biomass and the flame retardant are mixed, they are subjected to instantaneous high temperature treatment. While the graphene polymer is prepared by the biomass, the flame retardant is adsorbed on the graphene polymer to obtain a graphene flame retardant composite. The weight percentages of the raw materials are: 5-20% of flame retardant, 80-95% of biomass, and the sum of the weight percentages of the two is 100%; The graphene flame retardant composite, polyamide, a compatibilizer and polyolefin are mixed to obtain a mixture; The weight percentage of each raw material is: 5-10% of graphene flame retardant composite, 5-10% of polyamide, 2±0.1% of compatibilizer, and the balance is polyolefin, and the sum of the weight percentages of each raw material is 100%; The mixed material is melted, sheared and dispersed to obtain a composite material; The composite material is sequentially subjected to injection molding and hot pressing to obtain a high-strength, wear-resistant, flame-retardant and antistatic conveyor roller.

2. The method for preparing the high-strength, wear-resistant, flame-retardant and antistatic conveyor roller according to claim 1, characterized in that: The conditions for instantaneous high temperature treatment are: treatment at 2000-3500°C for 30-50ms.

3. The method for preparing the high-strength, wear-resistant, flame-retardant and antistatic conveyor roller according to claim 1, characterized in that: The flame retardant is selected from one or more of phosphorus flame retardants, metal hydroxides, and ammonia flame retardants.

4. The method for preparing the high-strength, wear-resistant, flame-retardant and antistatic conveyor roller according to claim 1, characterized in that: The conditions for melt shear dispersion are: 180-300°C, 1-5MPa.

5. The method for preparing the high-strength, wear-resistant, flame-retardant and antistatic conveyor roller according to claim 1, characterized in that: The polyamide is selected from one or more of nylon 6, nylon 66, nylon 11 and nylon 12.

6. The method for preparing the high-strength, wear-resistant, flame-retardant and antistatic conveyor roller according to claim 1, characterized in that: The compatibilizer is selected from one or more of maleic anhydride, dicumyl peroxide, ethylene-acrylate, and polyolefin elastomer.

7. The method for preparing the high-strength, wear-resistant, flame-retardant and antistatic conveyor roller according to claim 1, characterized in that: The polyolefin is selected from one or more of high-density polyethylene, linear low-density polyethylene, isotactic polypropylene, syndiotactic polypropylene and atactic polypropylene.

8. The method for preparing the high-strength, wear-resistant, flame-retardant and antistatic conveyor roller according to claim 1, characterized in that: The injection molding conditions are: 180-220°C, 5-15MPa.

9. The method for preparing the high-strength, wear-resistant, flame-retardant and antistatic conveyor roller according to claim 1, characterized in that: The conditions for hot pressing are: 200-250°C, 1-5MPa.

10. A high-strength, wear-resistant, flame-retardant and antistatic conveyor roller made by the preparation method according to any one of claims 1 to 9.